A Brief Review on Solanum nigrum - A. Siddiqui, Anees (Asian Journal of Chemistry, 2010)
Solanum nigrum Linn (N.O. Solanaceae) commonly known as black nightshade or mako is widely distributed throughout India. Its berries are used in Ayurvedic and Unani systems of medicine as hepatoprotective, laxative, alternative, aphrodisiac, tonic and diuretice. Freshly prepared extract of plant is effective in cirrhosis of liver and opium poisoning1. The whole plant of Solanum nigrum L. has been traditionally used in various types of cancers in China2.